Prevalence of thyroid dysfunction and its correlation with CD4 count in newly-diagnosed HIV-positive adults – a cross-sectional study. (November 2015) - Dev, Nishanth; Sahoo, Ratnakar; Kulshreshtha, Bindu; Gadpayle, A K; Sharma, S C
Prevalence of subclinical hypothyroidism in HIV-positive patients is reported to be high in those with severe immune deficiency. However, there is paucity of literature in newly-diagnosed HIV-positive population. Our aim was to estimate the prevalence of thyroid dysfunction and study its correlation with CD4 count in this population. In this cross-sectional study, patients presenting to the antiretroviral therapy clinic were screened with thyroid function tests, including thyroid stimulating hormone, free triiodothyronine, free thyroxine, and anti-thyroid peroxidase antibody levels at the time of diagnosis. Two hundred and twenty-five HIV-positive and an equal number of healthy volunteers were enrolled. The mean (SD) CD4 count in the study group was 147.1 (84) and 70.7% had advanced immune deficiency with CD4 count <200 cells/µL. The overall prevalence of thyroid dysfunction was 75.5% in the study group and 16% in the control group. Subclinical hypothyroidism was the commonest abnormality noted in almost 53%. Significant correlation was observed between CD4 count and thyroid stimulating hormone, free triiodothyronine, and free thyroxine levels ( r = −0.86, r = 0.77, and r = 0.84, respectively, p < 0.0001 for all). The present study demonstrated high prevalence of thyroid dysfunction in HIV-positive patients. The dysfunction is subclinical in most cases and correlates well with declining CD4 counts.